2016
DOI: 10.3109/0886022x.2016.1148558
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute kidney injury after acute myocardial infarction

Abstract: Objectives: To study the risk factors for acute kidney injury (AKI) in-patients with acute myocardial infarction (AMI). Methods: A total of 1371 cases of adult in-patients with AMI in the First People's Hospital of Changzhou from January 2008 to December 2012 were retrospectively analyzed. Based on the occurrence of AKI diagnosed according to the 2012 KDIGO AKI criteria, they were divided into AKI group and non-AKI group and further into conservative treatment groups, coronary angiography (CAG) groups, and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…The etiologies attributed to the development of AKI in the setting of ACS are diverse and include contrast-induced AKI (CI-AKI) following coronary angiography and especially PCI, hemodynamic instability with compromised renal perfusion (i.e., cardiogenic shock, mechanical complication, or arrhythmias), volume status changes, medications (e.g., nitroglycerine, diuretics, ACE I/ARBs), atheroembolism during PCI, ischemia driven alteration in the function and structure of epithelial cells, non-cardiovascular complications such as infections or inflammatory states as well as patient-associated comorbidity and predispos-ing risk factors (prior chronic kidney disease, diabetes, increased age, etc.) [24][25][26][27][28][29][30][31]. CI-AKI is a prominent and widely investigated mechanism for AKI in ACS patients following coronary angiography/PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies attributed to the development of AKI in the setting of ACS are diverse and include contrast-induced AKI (CI-AKI) following coronary angiography and especially PCI, hemodynamic instability with compromised renal perfusion (i.e., cardiogenic shock, mechanical complication, or arrhythmias), volume status changes, medications (e.g., nitroglycerine, diuretics, ACE I/ARBs), atheroembolism during PCI, ischemia driven alteration in the function and structure of epithelial cells, non-cardiovascular complications such as infections or inflammatory states as well as patient-associated comorbidity and predispos-ing risk factors (prior chronic kidney disease, diabetes, increased age, etc.) [24][25][26][27][28][29][30][31]. CI-AKI is a prominent and widely investigated mechanism for AKI in ACS patients following coronary angiography/PCI.…”
Section: Discussionmentioning
confidence: 99%
“…A burst of immunological and inflammatory activation were the potential causes of further renal injury [12]. Several studies proposed certain risk factors for AKI secondary to AMI, including advanced age [6, 13, 14], admission hyperglycemia [15, 16], impaired renal function at presentation [5, 6, 13], and prolonged duration to coronary reperfusion [17]. There were some prediction scores of AKI after the percutaneous coronary intervention (PCI) for AMI [1821].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AKI, elevated with the decreased LVEF, can be explained by a dramatic decrease in cardiac output after AMI, resulting in a decrease in renal perfusion, as well as the activation of renin angiotensin–aldosterone system (RAS) and cascade actions. Our prophase research also found lower LVEF levels in AKI patients [55 (48, 61) vs. 58 (51, 62), p < .001], but multivariate regression equation did not suggest an independently association with AKI [ 40 ]. In this study, LVEF was not even an independent factor for mortality among AMI patients.…”
Section: Discussionmentioning
confidence: 64%